STRATEGI PENGGUNAAN MODEL PEMBELAJARAN DIGITAL UNTUK MENINGKATKAN KOMPETENSI GURU DI SDN DEWI SARTIKA - Lestiawati, Lastri; Iriantara, Yosal; Yoseptri, Ricky; Afghan, Arief Nur; Kuntari, Ari Kukuh; Nurbaini, Ani (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
Technological advances have brought significant changes to the world of education, including at the elementary school level. This article discusses strategies for using digital learning models to improve teacher competency at SDN Dewi Sartika. By integrating technology into the learning process, teachers' pedagogical and professional competence is hoped to increase significantly. This research uses a qualitative descriptive method with data obtained through interviews, observation and literature study. The research results show that the application of digital learning models, such as the Learning Management System (LMS), learning videos, and interactive applications, can effectively support teacher competency development. However, there are several challenges in implementing this model, such as limited technological infrastructure, lack of digital literacy among some teachers, and resistance to changes in traditional learning methods. To overcome these obstacles, ongoing support is needed in providing technological facilities, relevant training programs, and school policies that support the development of digital-based teacher competencies. In conclusion, the digital learning model is an innovative solution that can help the development of teacher competency at SDN Dewi Sartika. With the proper implementation strategy, this model improves the quality of learning and equips teachers with relevant skills in the digital transformation era. This research recommends strengthening collaboration between schools, teachers and stakeholders to ensure the sustainability of the implementation of digital learning models.